Capital Markets Integration and Economic Growth - Otilia-Roxana Oprea; Ovidiu Stoica (Montenegrin Journal of Economics, 2018)
Nowadays, the capital markets have an increasing role and weight in the modern financial systems. Economic (and financial) integration should allow companies to access more sophisticated and competitive capital markets for accelerating the economic development. The purpose of this paper is to investigate the impact of the capital markets’ integration on economic growth in the EU countries and identify the main factors through which capital markets’ development influences economic growth, especially in an economic (and monetary) union. In this article we had used the Autoregressive Distributed Lag model for the EU countries during 2004-2016. According to the results, we can say that the integration of capital markets has a positive impact on economic growth, and the main factors in which the capital market positively affects economic growth are stock market capitalization, capital mobility, value traded, stock indices, immigrants, and, to a greater extent, small, foreign portfolio investment. Policymakers in this area should pay attention reducing external debt, which is a significant proportion of foreign capital inflows, and encouraging the foreign portfolio investments to stimulate stock market development and growth, reducing extreme stock price volatility, fostering a good correlation of savings with investment (i.e. capital mobility), boosting volume growth transactions on stock markets, they should guarantee full employment through fiscal policy, monetary policy and trade policy as stated, by counteracting private sector or trade investment volatility, and reducing inequality, and stimulating increased labor mobility from developed countries to the least developed to balance the economy.